1996
DOI: 10.1128/aac.40.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nifedipine, metronidazole, and nitric oxide donors on spore germination and cell culture infection of the microsporidia Encephalitozoon hellem and Encephalitozoon intestinalis

Abstract: Two species of microsporidia, Encephalitozoon hellem and Encephalitozoon intestinalis, were isolated from AIDS patients and cultured in green monkey kidney cells. A spore germination assay and a cultured-cell infection assay were used to test the efficacy of candidate antiparasitic agents. The calcium channel blocker nifedipine, metronidazole, and two nitric oxide (NO) donors, S-nitroso-N-acetylpenicillamine and sodium nitroprusside, were tested in the two assays. Nifedipine (10 ؊8 M) significantly inhibited E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 31 publications
(64 reference statements)
0
29
0
Order By: Relevance
“…The mode of action of metronidazole on microsporidia is uncertain, but it slows or inhibits intracellular parasite proliferation and differentiation in vitro with E. intestinalis in human cell culture (He et al, 1996). We found no antimicrosporidial action by metronidazole in grasshoppers at the concentration used.…”
Section: Comparison Of Therapeutic Efficacy Of Different Antibiotics mentioning
confidence: 94%
See 1 more Smart Citation
“…The mode of action of metronidazole on microsporidia is uncertain, but it slows or inhibits intracellular parasite proliferation and differentiation in vitro with E. intestinalis in human cell culture (He et al, 1996). We found no antimicrosporidial action by metronidazole in grasshoppers at the concentration used.…”
Section: Comparison Of Therapeutic Efficacy Of Different Antibiotics mentioning
confidence: 94%
“…Metronidazole, first used to treat trichomoniasis and later amebiasis, giardiasis, and anaerobic infections, has been used to treat microsporidiosis (He et al, 1996). The mode of action of metronidazole on microsporidia is uncertain, but it slows or inhibits intracellular parasite proliferation and differentiation in vitro with E. intestinalis in human cell culture (He et al, 1996).…”
Section: Comparison Of Therapeutic Efficacy Of Different Antibiotics mentioning
confidence: 99%
“…Mucin or polyanions (Pleshinger & Weidner 1985;Weidner et al 1995), hydrogen peroxide (Kudo 1918;Lom & Vavra 1963;Hashimoto et al 1976;Leitch et al 1993;He et al 1996), low-dose ultraviolet (UV) radiation (Undeen & Epsky 1990), and a Na + ionophore monensin (Frixione et al 1994) have also been used to trigger discharge. Inhibitors of spore discharge include concentrated alcohols (Kudo 1918), 0.01-0.1 M magnesium chloride (Malone 1984), ammonium chloride (Undeen 1978;Undeen & Avery 1988a;Undeen & Epsky 1990), low salt concentrations (10-50 mM) (Undeen 1978), sodium fluoride (Undeen & Avery 1988b), 1.8 M sucrose (Undeen 1978), silver ions (Ishihara 1967), gamma radiation ), UV Phosphate-buffered saline, pH 8.5-9.0, containing 0.1-0.5% porcine mucin Weidner et al (1984) Spraguea lophii a Storage in 0.05 M Hepes, pretreatment in 10 −5 M Ca 2+ , pH 7, followed by Hepes, pH 9.5, containing 2% mucin Weidner et al (1995) Thelohania californica Mechanical pressure Kudo and Daniels (1963) …”
Section: Glugea Hertwigimentioning
confidence: 99%
“…light (Undeen & Van der Mer 1990;Whitlock & Johnson 1990), temperatures greater than 40°C (Whitlock & Johnson 1990), a microfilament disrupter (cytochalasin D), a microtubule disrupter (demecolcine), itraconazole , metronidazole (He et al 1996), and the nitric oxide donors S-nitroso-N-acetylpenicillamine and sodium nitroprusside (He et al 1996). Calcium chloride (0.001-0.1 M) has been found to inhibit spore germination in some studies (Ohshima 1964a(Ohshima , 1964bIshihara 1967;Undeen 1978Undeen , 1983Weidner 1982;Malone 1984), while 0.2 M CaCl 2 at pH 9.0 (Pleshinger & Weidner 1985) and 1 mM CaCl 2 He et al 1996) as well as calcium ionophore A 23187 (Weidner 1982;Pleshinger & Weidner 1985) promoted discharge in other studies.…”
Section: Vavraia Oncoperaementioning
confidence: 99%
“…The role of NO in spore germination is unclear. Both germination of Aspergillus fumigatus resting conidia and the protozoan Encephalitozoon hellem and Encephalitozoon intestinalis were inhibited when treated with various NO donors (He et al, 1996;Kunert, 1995). However, it has been reported that NO both promotes germination and decreases viability of the blastoconidia of Candida albicans (Abaitua et al, 1999).…”
Section: Introductionmentioning
confidence: 97%